Kepemimpinan Sebagai Agen Penguatan Moderasi Beragama di Lingkungan Masyarakat Multikultural - Hidayah, Ulil (Proceedings of Annual Conference for Muslim Scholars, 2023)
Islam is the majority religion in Indonesia which is dominated by two major Islamic organizations namely Muhammadiyah and Nahdlatul Ulama'. The STAI Muhammadiyah Probolinggo campus as the object of this research is a miniature picture of Islam in Indonesia which is dominated by two groups Nu and Muhammadiyah which aims to foster harmony of diversity groups through a moderate leadership model. By applying the Grounded Theory method that focuses on developing theories from empirical data based on the results of observations, interviews and document analysis inductively about a person's behavior pattern. The results of this study provide an overview of moderate leaders who are not fanatic about one particular group even though it is their identity and the policies enacted are beneficial for the interests of each group. Thus the development of this research contributes to a deeper understanding of the role and model of leadership as an agent of strengthening religious moderation in various domains of multicultural society